Influence of Manure And Pgr Cosentration OnGrowth of Pakchoy (Brassica Chinensis) - Usman Nur Rohman; Nurlina; Nurul Huda (Faculty of Agriculture, Merdeka University Surabaya, 2017)
The purpose of this research is to determine interaction between composition of growing medium, PGR concentration to growth, influence of composition of growing medium toward growth and harvest of pakchoy. The present study uses factorial randomized group design consisting of two factors with three replicates and 2 sample plants. Factor I is growing medium composition of 3 levels while factor II is a level 3 PGR concentration. The composition of these factors is factor I: M 3 garden soil: 1 manure, M 2 = 2 garden soil: 2 Manure, M 3 = 1 = 1 garden soil: 3 manure. Factor II consists of: K = 2 ml/liter of water, K 2 = 4 ml/liter of water, K = 6 ml / liter of water. Results from this study indicate that the combined treatment of manure and PGR concentration has significant effect on observation of plant length at 28 days of age. However, it does not give real interaction to variables of number of leaves, plant length, and gross at all ages of observation. The use of manure has significant effect on all observation variables. The highest average plant length, leaf number, and highest gross were obtained at the treatment of M 2 3 (2 garden soil: 2 manure). Treatment of PGR concentration had significant effect on all observation variables. Average length of plants, number of leaves, and highest gross were obtained at treatment of K 2 ml / ltr water.